‘Women’ and ‘Sexuality’ in the 18th and 19th century english novels: a reading of Eliza Haywood and Thomas Hardy - Annanya, Nusrat Karim (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.